Infant Botulism in the Very Young Neonate: A Case Series - Jackson, Laura; Madan-Khetarpal, Suneeta; Naik, Monica; Michaels, Marian G.; Riley, Melissa (American Journal of Perinatology Reports, 2017)
Background Though botulism is a rare disease overall, all infants younger than 1 year of age are at risk of contracting infant botulism, the most prevalent form reported in the United States. Nonetheless, infant botulism is frequently omitted from the differential diagnosis of the very young neonate exclusively due to age, and the diagnosis is often only considered secondarily after a costly and prolonged work up is undertaken. Delayed diagnosis can lead not only to unnecessary testing but also to prolonged hospital stay and increased morbidity.Case This case series highlights three critically ill neonates, all younger than 30 days, who presented to our neonatal intensive care unit and were eventually diagnosed with infant botulism. The initial diagnostic dilemma is described for each of these patients and highlights the importance of early recognition of the main symptoms, in addition to consideration of important potential coinciding conditions.
Keywords: neonatology; infant botulism; BIG-IV